Investigation of dielectric properties of Fe and Co coated thin films on PbZrTiO3 - Dilek Kafkas; Ahmet Demirkaya; Aliye Kahyaoğlu (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2024)
PbZr1-xTixO3 ceramic material, which has ferroelectric-piezoelectric properties, attracts great attention from researchers due to its electrical and electromechanical properties. In this study, Fe and Co materials with ferromagnetic properties were coated separately on the ferroelectric-piezoelectric PbZr0.5Ti0.5O3 (PZT) ceramic material by vacuum evaporation technique. The variation of dielectric properties such as dielectric constant, dielectric loss, loss tangent, cole-cole diagram of the prepared thin films with frequency was examined. Dielectric constant, dielectric loss, loss tangent, cole-cole diagram of pure PZT, Fe-coated PZT and Co-coated PZT thin films were measured with an impedance analyzer as a function of frequency (in the range of high frequency) at room temperature.